OP0233 THE IMPACT OF EXTRA-ARTICULAR MANIFESTATIONS ON THE CHOICE OF TNF INHIBITOR IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS IN THE BSRBR-AS REGISTER. (June 2019) - Derakhshan, Mohammad H.; Dean, Linda; Jones, Gareth T.; Macfarlane, Gary; Siebert, Stefan; Gaffney, Karl
Abstract : Background: Axial spondyloarthritis (axSpA) is associated with important extra-articular manifestations (EAMS), most notably acute anterior uveitis (AAU), inflammatory bowel disease (IBD) and psoriasis, which may influence the choice of biologic agent used to treat axSpA. Objectives: To examine the factors associated with choice of 1st TNF inhibitor (TNFi) for the treatment of axSpA. Methods: Clinical and patients-reported outcomes of 2420 patients with axSpA from 83 rheumatology centres in the United Kingdom were collected as part of the British Society for Rheumatology Biologics Register in Ankylosing Spondylitis (BSRBR-AS). History of pre-treatment AAU, IBD and psoriasis were analysed to explore their association with the choice of 1st TNFi. This preference was also examined in relation to other demographic and background factors. These associations were analysed using univariable and multivariable logistic regression models, considering necessary interaction terms. Results: First-line biologic data was available for 441 patients, compromising of 284 (64.4%) adalimumab (ADA), 109 (24, 7%) etanercept (ETA) and 48 (10.9%) certolizumab (CZP). Pre-treatment EAMS in the entire cohort were 568 cases of AAU, 247 IBD and 264 psoriasis. Prior diagnosis of AAU was associated with a choice of ADA over the other TNFi (ETA and CZP) [OR=3.13, 95% CI: 1.78 – 5.52). Conversely, a diagnosis of AAU was associated with less preference for ETA (OR=0.16, 95% CI: 0.07 – 0.37) compared with ADA and CZP. The choice of a particular TNFi was not associated with HLA-B27, age, gender, axSpA disease duration, BASDAI or BASFI scores. When IBD and psoriasis, and interactions with AAU, were considered in multivariable models (Table), a diagnosis of either AAU or IBD was associated with more preference of ADA versus other TNFi. In contrast, diagnosis of either AAU or IBD was associated with significantly less preference of ETA over other TNFi. The preference of CZP was not associated with presence any pre-treatment extra-articular manifestations. Conclusion: EAMs appear to play an important role in the choice of TNFi in axSpA. Patients with previous AAU and IBD are more likely to be prescribed ADA and less likely to receive ETA, consistent with the superior efficacy of monoclonal TNFi for these conditions. The presence or absence of EAMS did not influence the use of CZP, although small sample size might explain the lack of associations. Future work will determine whether EAMS influence TNFi survival, or effectiveness, and whether this varies between agents. Acknowledgement: British Society of Rheumatology Disclosure of Interests: Mohammad H. Derakhshan: None declared, Linda Dean: None declared, Gareth T. Jones Grant/research support from: Have received research grants (not current) from Abbvie and Pfizer. Have received research grants (not current) from the British Society for Rheumatology, who received the funds from Abbive, Pfizer and UCB. Have received research grant (current) from the British Society for Rheumatology, who received the funds from Celgene., Gary Macfarlane Grant/research support from: Have received research grants (not current) from Abbvie and Pfizer. Have received research grants (not current) from the British Society for Rheumatology, who received the funds from Abbive, Pfizer and UCB. Have received research grant (current) from the British Society for Rheumatology, who received the funds from Celgene., Stefan Siebert Grant/research support from: AbbVie, Novartis, Pfizer, Janssen, BMS, Celgene, UCB, and Boehringer Ingelheim, Consultant for: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Speakers bureau: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Karl Gaffney Grant/research support from: Abbvie, Pfizer, Consultant for: Abbvie, Lilly, Novartis, UCB, Speakers bureau: Abbvie, Biogen, Gilead, Lilly, Novartis, UCB